Investigating the impact of spring support stiffness on dynamic buckling of imperfect steel trusses - Pham Van Dat; Dao Ngoc Tien; Ta Duy Hien; Phu-Cuong Nguyen (Results in Engineering)
This paper investigates the influence of elastic support stiffness on the dynamic stability of imperfect planar steel trusses. First, a generalized model for elastic supports is proposed, which is then applied to study the dynamic stability of imperfect trusses. Several factors contribute to imperfections in truss structures, including variations in member length, load distribution, nodal coordinates, and support stiffness. This study focuses on two main imperfections: member length imperfections and loading imperfections. The large displacement problem of trusses is addressed using a combination of the Euler formulation and the finite element method (FEM). The governing equations are derived based on the principle of virtual work and solved using the Newton-Raphson iterative algorithm. The findings reveal that elastic support stiffness significantly affects the critical dynamic load of imperfect planar steel trusses. The results emphasize the importance of considering support stiffness when analyzing the dynamic stability of these structures.